Transformation of Consumption Behavior of the Poor in the Case of Malnutrition: Health Sociology Study with Participatory Approach in Makassar City, Indonesia - Alim, Andi; Agustang, Andi; Adam, Arlin (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Poor families understand, interpret, and interpret the balanced nutritional content of food and drinks consumed daily according to their experiences and the environment that hits them. The assumption of this research assumes that there is a change in consumption behaviour due to the knowledge of the poor which is formed by advertisements with very high exposure and frequency every day. AIM: This study aims to explore the transformation of consumer behaviour that causes the process of malnutrition and the framework of capitalism in marginalizing the poor to fulfil their nutritional needs. METHODS: This study uses qualitative research methods with a critical approach paradigm. RESULTS: This study found that malnutrition among the poor in Makassar City is caused by the wrong knowledge of the community in understanding nutritious food. Meanwhile, children’s tastes are formed based on environmental influences which are generally constructed by industrially processed foods. Another finding is that the framework of capitalism in marginalizing the poor to fulfil their nutritional needs operates in the form of massification of industrial processed food and beverage products; the intensity of advertising for nutritious food products, the presence of online food ordering technology; the construction of the lifestyle of the person who belongs; and the emergence of outlets/shops serving fast food. CONCLUSIONS: The critical paradigm used in this study produces sociological actions that need to be taken to avoid the trap of food capitalism for poor families through community empowerment movements towards healthy shopping behaviours.